Applying analytical hierarchy process in ranking of the effective indices on competitiveness of the wooden furniture industry in Iran - Elham Gudarzi (Regional Information Center for Science and Technology (RICeST), 2015)
One of major causes of the failure production companies in the international markets is referred to the lack of their competitiveness in comparison with competitors. Therefore, the purpose of this study were determining and ranking of the effective indices on competitiveness of Iran’s furniture industry by analytical hierarchy process. ّFor this purpose, reviewing and investigating of researches carried out by others and interviewing with a numbers of especialista,the effective indices on competitiveness of Iran’s wooden furniture industry divided into the 4 main groups and 19 sub-indices.Importance degree of the indices and sub-indices were determined after collecting experts opinion by AHP method.The results showed that mainindicators economic, technical, materials, human being indices have highest weight values respectively. Successful designing sub-indices was dramatically higher than the other sub-indices and after that the sub-indices of raw materials, sustainable managem ent, professional human resources, standard development, sustainable supply, branding have allocated highest priority in AHP method respectively.